2014
DOI: 10.1016/j.clcc.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Progression-Free Survival Remains Poor Over Sequential Lines of Systemic Therapy in Patients With BRAF-Mutated Colorectal Cancer

Abstract: Background BRAF mutations occur in 5–10% of metastatic colorectal cancers and are biomarkers associated with a poor prognosis. However, the outcomes with standard chemotherapy over sequential lines of therapy in a large cohort of patients with BRAF-mutant tumors have not been described. Methods We searched the MD Anderson Cancer Center databases for patients with colorectal cancer patients and identified BRAF mutations between December 2003 and May 2012. Patients were analyzed for clinical characteristics, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 35 publications
6
88
0
2
Order By: Relevance
“…Other studies have reported similar BRAF mutation prevalence in mCRC patients to those we report [10,12,[21][22][23][24][25][26][27]. Our exploratory analysis of BRAF mutation prevalence by demographic and clinical factors found increased prevalence in females versus males, colon versus rectal cancer and in ECOG PS 0 versus 1/2.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Other studies have reported similar BRAF mutation prevalence in mCRC patients to those we report [10,12,[21][22][23][24][25][26][27]. Our exploratory analysis of BRAF mutation prevalence by demographic and clinical factors found increased prevalence in females versus males, colon versus rectal cancer and in ECOG PS 0 versus 1/2.…”
Section: Discussionsupporting
confidence: 85%
“…Our exploratory analysis of BRAF mutation prevalence by demographic and clinical factors found increased prevalence in females versus males, colon versus rectal cancer and in ECOG PS 0 versus 1/2. Other studies have reported increased BRAF mutation prevalence in older versus younger patients, females versus males, right-sided versus left-sided and mucinous versus tumours [25,26].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…B mutant aCRC is consistently associated with poor overall survival (OS) and progression free survival (PFS) in case series [1] and randomised controlled trials (RCTs). [2] In a recent RCT of previously untreated aCRC, median OS was 13.4 months in Bmutant patients compared with 37.1 months in and wildBtypes.…”
Section: Introductionmentioning
confidence: 99%